Transdiciplinarity and Active Methods for Teaching Literature to Children: A Literature Review - Peña-Acuña, Beatriz (2026)
This study seeks to examine contemporary research trends on transdisciplinary innovation interventions employing active methodologies for children's literary education. The research methodology involved a bibliographic review centered on the critical study of academic papers over the past decade, sourced from databases like Web of Science, Scopus, and ERIC. The data indicate that transdisciplinary strategies in children's literary education are more common in English-speaking countries, implying a higher incorporation of novel methodologies. The primary educational trends identified include process-oriented learning, gamification, and the integration of Information and Communication Technologies (ICT). These tools facilitate active student participation and enhance their engagement in the educational experience. Furthermore, the implementation of these strategies has demonstrated efficacy in educational environments focused on enhancing literary skills and augmenting reading comprehension. Research reveals substantial positive correlations between students' comprehension of literary concepts and their motivation levels in transdisciplinary methods. A holistic approach enables students to attain a deeper understanding of literary subjects by integrating other disciplines and perspectives. In summary, transdisciplinary interventions and active approaches significantly improve instructional practices and educational results in children's literary education.